Hierarchical Assembly of Monodisperse Hydroxyapatite Nanowires and Construction of High‐Strength Fire‐Resistant Inorganic Paper with High‐Temperature Flexibility. Issue 4 (6th March 2017) - Li, Heng; Zhu, Ying‐Jie; Jiang, Ying‐Ying; Yu, Ya‐Dong; Chen, Feng; Dong, Li‐Ying; Wu, Jin
Abstract: High‐strength flexible inorganic paper with fire‐resistant and adiabatic properties is highly demanded in various high‐temperature applications. However, constructing inorganic paper that not only has high strength and high flexibility at room temperature but also can prevent the high‐temperature‐induced friability is still a great challenge. Inspired by the hierarchical structure and excellent mechanical properties of the tooth enamel, we have developed a systematic approach for the bottom‐up fabrication of multi‐hierarchical fire‐resistant hydroxyapatite (HAP) nanowire paper with balanced tensile strength and flexibility that includes four steps: (1) the synthesis of monodisperse HAP nanowires from the molecular level to the nanoscale; (2) the self‐assembly of HAP nanowires into long fibers and two‐dimensional (2D) nanowire networks from the nanoscale to the mesoscale; (3) the layered assembly of 2D nanowire networks into the highly flexible high‐strength fire‐resistant paper from the mesoscale to the macroscale; (4) reinforcing the HAP nanowire paper with inorganic additives to enhance the tensile strength and to overcome the high‐temperature‐induced pulverization. By adopting this strategy, the mechanical properties of the fire‐resistant HAP nanowire paper are greatly improved. The experimental results show that the tensile strength of the as‐prepared HAP nanowires‐based inorganic paper is greatly enhanced to ≈15 MPa, which is close to that of the commercial copying paper, and the A4‐sized HAP nanowires‐based inorganic paper is highly flexible and can be directly printed using a commercial printer. Owing to the synergistic effect of all components and the unique hierarchical structure, the as‐prepared fire‐resistant HAP nanowire paper can also preserve well its high flexibility even under high‐temperature conditions. Abstract : A strong flexible fire‐resistant hydroxyapatite (HAP) paper based on network‐structured HAP nanowires is reported. A new low‐cost method is also developed for the large‐scale synthesis of HAP nanowires using water as the only solvent.